'Moving the Kaleidoscope' to see the effect of creative personality traits on creative thinking dispositions of preservice teachers: The mediating effect of creative learning environments and teachers' creativity fostering behavior. (September 2021) - Ayyildiz, Pınar; Yilmaz, Adem
Highlights: Personality traits have been identified as a series of factors that directly affect creative thinking dispositions. In conjunction with this, a creative learning environment and fostering teacher behaviors have a characteristic that affect creative thinking dispositions in company with creative personality traits. To this end, individual aptitudes of learners should be triggered with the assistance of appropriate learning environments as well as the right teacher behaviors which find and create the space and time for creativity work. Creative thinking dispositions occur at a higher level in women compared to men. Also, as the grade level increases, knowledge and experience increase indirectly and these influence creative thinking dispositions. On that account, education curricula, also covering co-curricular and extra-curricular projects and collaborative/voluntary work, need to be revisited so that creativity is addressed properly, and it should be ensured there is room for males to improve their creative behaviors as much as possible throughout grade levels. It was determined that the participating pre-service teachers in the department of mathematics and science have higher levels of creative thinking dispositions than the pre-service teachers studying in the department of educational sciences and primary education. It can be propounded that analytical, numerical, and algorithmic skills affect the creative thinking dispositions indirectly thereby elevating these. Assuring the improvement of analytical, numerical and algorithmic skills for all departments will be worthwhile and to do so some courses like coding can be incorporated into the curricula, which can help develop 21st century skills supplementary to and as part of creativity and creative behaviors. Abstract: This study aimed to examine the effect of creative personality traits on creative thinking dispositions through creative learning environments and teacher behaviors that foster creativity. Gender, department, and grade level are also defined as common variables. 1320 teacher candidates who were selected with purposeful and appropriate sampling supported the research. 726 of these individuals are females and 594 are males. Participants in the study are teacher candidates from education faculties, science, mathematics, classroom, and educational sciences departments. Whilst determining the participants, attention was paid to the selection of those who have previously taken courses that are directly or indirectly related to creative thinking, critical and analytical thinking, entrepreunership and creativity. Descriptive and inferential statistics were used in the analysis of the research data. Aside from this, the mediation effect of variables was performed using Hayes' number 6 serial multiple mediation analysis models. As a result of the research, it was found that creative personality traits positively predicted creative thinking dispositions through the learning environment and teachers' fostering behaviors. The creative learning environment and teachers' fostering behaviors similarly have a positive mediating effect.